Effect of forearm compression sleeves on the exercise performance of sport climbers - Sas-Nowosielski, K.; Kluska-Cyba, K. (Journal of Kinesiology and Exercise Sciences, 2024)
Background: Compression garments, i.e. elastic garments with an engineered compression gradient, are widely used in rehabilitation and sport. It is used in sport to improve performance and reduce discomfort during exercise and lower the risk of injury. However, the question of the actual effectiveness of this type of support is controversial, and there is little research in the field of sport climbing, The aim of this study was to investigate the effect of forearm compression garments on the performance of climbing-specific exercises. Methods: Eleven elite climbers (35.9±7.8 years, 177.7±7.1 cm and 70.3±7.9 kg, IRCRA climbing level 24.6±1.9) took part in a placebo-controlled cross-over design study. The climbers used compression or placebo sleeves, while performing two trials: an intermittent campus board exercise (`reaches`) and a traverse climb. During the trials, the number of repetitions and, during the campus board trial, maximum and average power were recorded. Power measurements were taken using a Gyko inertial sensor. Results: Under compression, statistically significant differences were only observed for the subjective sensation of forearm `pump` on the campus board trial (p=0.007, ES=0.64). In the placebo condition, the total number of "reaches" on the campus board, as well as the number of interceptions and time spent on the traverse were statistically significantly lower compared to baseline (respectively, p=0.032, ES=0.74; p=0. 025, ES=0.49 and p=0.013, ES=0.64). Conclusion: For elite climbers performing specific climbing activities, forearm compression doesn`t significantly improve their performance compared to baseline, but it can prevent it from deteriorating to some extent.